Unveiling Inter-Market Reactions to Different Asset Classes/Commodities Pre- and Post-COVID-19: An Exploratory Qualitative Study - Siddhartha S. Bannerjee; Rekha Pillai; Mosab I. Tabash; Mujeeb Saif Mohsen Al-Absy (Economies)
Comprehending intermarket relationships among asset classes/commodities and the changing dynamics among the gold, bitcoin, and oil markets under high or low-volatility indexes is now imperative for investors. This paper presents a qualitative study to elicit expert views on the relationships between two major commodities (gold and oil) and bitcoin, specifically emphasizing the pre- and post-COVID-19 era. The thematic analysis of 30 finance experts revealed gold as a safe haven and portfolio diversifier; however, it has lost importance as an inflation hedge post-COVID-19 (2020–2022). Moreover, findings indicated that bitcoin was not a substitute for gold and that there was a positive correlation between gold and oil and the gold volatility index (VIX). Furthermore, there was a negative correlation between the oil VIX and the bitcoin VIX, with no correlation between the gold–bitcoin or oil–bitcoin nexus. These findings are pertinent for investors and scholars in the context of portfolio allocation/portfolio design that comprise these vital asset classes/commodities.